2011
DOI: 10.1111/j.1600-0706.2011.19832.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and spatial analyses reveal links between colony‐specific foraging distance and landscape‐level resource availability in two bumblebee species

Abstract: Foraging distance is a key determinant of colony survival and pollination potential in bumblebees Bombus spp. However this aspect of bumblebee ecology is poorly understood because of the difficulty in locating colonies of these central place foragers. Here, we used a combination of molecular microsatellite analyses, remote sensing and spatial analyses using kernel density estimates to estimate nest location and foraging distances for a large number of wild colonies of two species, and related these to the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 56 publications
5
70
0
Order By: Relevance
“…It is therefore possible that the interspecific variation was too low to mediate any landscape effects. Interestingly it has been shown that several Bombus species (B. terrestris: Osborne et al 2008, B. pascuorum: Goulson et al 2010Carvell et al 2012, B. lapidarius: Carvell et al 2012, B. vosnesenskii: Jha and Kremen 2013 adjust their foraging ranges depending on the surrounding resource distribution and diversity. This may indicate that, at the spatial scales of resource distribution studied here, flight capacity itself (via its proxy thorax width) may not limit resource acquisition by bumble bees.…”
Section: Effects Of Morphological Traitsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is therefore possible that the interspecific variation was too low to mediate any landscape effects. Interestingly it has been shown that several Bombus species (B. terrestris: Osborne et al 2008, B. pascuorum: Goulson et al 2010Carvell et al 2012, B. lapidarius: Carvell et al 2012, B. vosnesenskii: Jha and Kremen 2013 adjust their foraging ranges depending on the surrounding resource distribution and diversity. This may indicate that, at the spatial scales of resource distribution studied here, flight capacity itself (via its proxy thorax width) may not limit resource acquisition by bumble bees.…”
Section: Effects Of Morphological Traitsmentioning
confidence: 98%
“…Genetic methods can be employed to more accurately estimate landscape wide colony densities (e.g. Carvell et al 2012), but was not possible to employ on our data set including 13 species. Plasticity in colony size is indeed a trait, which could potentially promote persistence through periods of variable forage availability.…”
Section: Potential Caveatsmentioning
confidence: 99%
“…The study was conducted on the Hillesden Estate, 1000 ha of farmland in Buckinghamshire, central England (51.95N,01.00W (Hinsley et al, 2010), small mammals, pollinators (Carvell et al, 2012) and invertebrates (Woodcock et al, 2010). Three levels of Environmental Stewardship management were established on plots of between 60 and 90 ha, each replicated five times in a randomised block design (see Hinsley et al, 2010 for further details).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, relatively common bumblebee species (e.g. Bombus pascuorum and Bombus lapidarius) in Britain may be somewhat buffered against landscape alteration due to their ability to forage and disperse over greater distances [40] than declining congeners [28,29]. Such dispersal by highly mobile, generalist species between habitat fragments may ameliorate the effects of landscape fragmentation on pollinator community evenness [27].…”
mentioning
confidence: 98%